Divergent lncRNA MYMLR regulates MYC by eliciting DNA looping and promoter‐enhancer interaction. (30th July 2019) - Kajino, Taisuke; Shimamura, Teppei; Gong, Shuyi; Yanagisawa, Kiyoshi; Ida, Lisa; Nakatochi, Masahiro; Griesing, Sebastian; Shimada, Yukako; Kano, Keiko; Suzuki, Motoshi; Miyano, Satoru; Takahashi, Takashi
Abstract: Long non‐coding RNAs (lncRNAs) function in a wide range of processes by diverse mechanisms, though their roles in regulation of oncogenes and/or tumor suppressors remain rather elusive. We performed a global search for lncRNAs affecting MYC activity using a systems biology‐based approach with a K supercomputer and the GIMLET algorism based on local distance correlations. Consequently, MYMLR was identified and experimentally shown to maintain MYC transcriptional activity and cell cycle progression despite the low levels of expression. A proteomic search for MYMLR ‐binding proteins identified PCBP2, while it was also found that MYMLR places a 557‐kb upstream enhancer region in the proximity of the MYC promoter in cooperation with PCBP2. These findings implicate a crucial role for MYMLR in regulation of the archetypical oncogene MYC and warrant future studies regarding the involvement of low copy number lncRNAs in regulation of other crucial oncogenes and tumor suppressor genes. Synopsis: Systems biology combined with biochemical analyses identifies a divergent long noncoding (lncRNA) termed MYC‐modulating lncRNA (MYMLR) as transcriptional regulator of proto‐oncogene MYC in cancer cells. The lncRNA MYMLR is divergent to the MYC locus and enriched in tumor tissues. MYMLR promotes MYC activity and cancer cell proliferation. MYMLR binds the RNA binding adapter protein PCBP2. MYMLR interaction with PCBP2 promotes proximity of an upstream enhancer to the MYC promoter increasing MYC expression. Abstract : A long‐noncoding RNA transcribed in close proximity to the MYC locus is acting in cis to facilitate MYC oncogene expression in cancer cells.